Strategi Pengembangan Sumber Daya Manusia dan Soft-Skill - Layli Rohmatillah; Misbahul Arifin; Akmal Mundiri (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
The rapid development of globalization and digitalization has intensified competition in the labor market, requiring human resources (HR) who are not only technically competent but also equipped with strong soft skills. This study aims to analyze effective strategies for developing human resources through the strengthening of soft skills in educational institutions and organizational settings. Employing a qualitative descriptive approach, the research is based on a comprehensive literature review of books, national and international journal articles, research reports, and relevant policy documents related to human resource development. Data were analyzed using content analysis to identify key themes, patterns, and strategic models of soft skill development, while source triangulation was applied to enhance the credibility and validity of the findings. The results indicate that communication, teamwork, problem solving, adaptability, resilience, and leadership are the most critical soft skills required across various sectors and job levels. The study also reveals that effective soft skill development requires integrated and sustainable strategies, including experiential training, continuous coaching and mentoring, project-based learning, integration of soft skills into formal curricula and employee onboarding programs, the reinforcement of supportive organizational culture, and the use of microlearning through digital learning pathways. Furthermore, comprehensive monitoring and evaluation mechanisms such as pre-post assessments, 360-degree feedback, performance indicators, and portfolio-based evaluation are essential to ensure measurable behavioral change and performance improvement. Despite challenges such as resistance to change, limited resources, and measurement difficulties, adaptive mitigation strategies can enhance implementation effectiveness. This study concludes that positioning soft skills as core competencies within long-term human resource development strategies is crucial for improving workforce readiness, organizational performance, and sustainability in an increasingly dynamic and uncertain work environment.